What attitude should parents have towards their children's future flourishing?. (March 2018) - Wolbert, Lynne S.; de Ruyter, Doret J.; Schinkel, Anders
This article explores how parents should relate to a particular (ideal) aim of education, namely, their children's future flourishing lives. The article asks three (sub)questions: (1) What does 'aiming for flourishing' mean? (2) In what sense should parents have expectations? (3) Is hope an appropriate attitude for parents with regard to their children's flourishing lives? It is argued that although there is also a place for expectations, an attitude of hope best captures how parents should relate to the educational aim of flourishing. Hope not only refers to the commitment and desire of realizing the object of one's hope but also implies a recognition of the limitations of human powers and of the uncertainties inherent in striving for an ultimate aim.